Case Study on Mutual Funds PT. Falcon Asia - Ayudya Adisti; Hans Samuel Listijono; Mutiara Fajrin Maulidya Mohammad; Judhith Vidya Dayati; Zain Lestya Pradana (Journal La Bisecoman, 2021)
to ascertain the reasons investors lost money with the PT Falcon Resources Management report. to provide sanctions and liability for investors who have lost in mutual funds This report uses the law technique. The second strategy was a conceptual. Secondary data are obtained by identifying and gathering data already released books, newspapers, magazines, journals, and internet portals. This result demonstrates that if an investor will demonstrate that the manager has defaulted or has violated the rule, he or she will be liable for compensation. Accountability is carried out in compliance with the rules and legislation in place. as a result of regulatory penalties, PT Falcon lost its business license. For criminal penalties, the offense will be punished under article 104 of the Capital Market Law with a sentence of ten years and a fine of fifteen billion credits. Meanwhile, the PT Falcon Manager will be charged in civil court on the grounds of Act Against the Law, and the investor will be rewarded if victorious.